2017
DOI: 10.1161/circresaha.116.309443
|View full text |Cite
|
Sign up to set email alerts
|

Social Integration and Reduced Risk of Coronary Heart Disease in Women

Abstract: Rationale Higher social integration is associated with lower cardiovascular mortality; however, whether it is associated with incident coronary heart disease (CHD), especially in women, and if associations differ by case fatality is unclear. Objectives This study sought to examine the associations between social integration and risk of incident CHD in a large female prospective cohort. Methods and Results 76,362 women in the Nurses’ Health Study (NHS), free of CHD and stroke at baseline (1992), were follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 55 publications
(52 reference statements)
3
46
1
1
Order By: Relevance
“…25 Also, they tended to have no spouse, suggesting lower social connection, which is a risk factor for CVD. 26 We also found an increased risk of CVD mortality with older maternal age at first delivery, especially in women with higher number of deliveries. Our result was supported by the finding from a previous study, which showed the higher age-adjusted mortality from risk of subarachnoid hemorrhage for maternal age ≥26 years at first delivery, compared to maternal age <25 years at first delivery.…”
Section: Discussionsupporting
confidence: 54%
“…25 Also, they tended to have no spouse, suggesting lower social connection, which is a risk factor for CVD. 26 We also found an increased risk of CVD mortality with older maternal age at first delivery, especially in women with higher number of deliveries. Our result was supported by the finding from a previous study, which showed the higher age-adjusted mortality from risk of subarachnoid hemorrhage for maternal age ≥26 years at first delivery, compared to maternal age <25 years at first delivery.…”
Section: Discussionsupporting
confidence: 54%
“…Data on incidence of MI and hypertension were not available for Mexico; therefore, we used data from the Epidemiological Surveillance System (; SINAVE), which reports new cases of ischemic heart disease (IHD), including MI, and separately reports hypertension new cases in Mexican women in 2012 (see Table S2). To approximate the incidence of MI, we multiplied the IHD incidence by 0.827, which is the estimated proportion of nonfatal MI cases from total IHD cases in a cohort of women (Chang et al, ). We assumed that the proportion of MI from IHD were the same across age groups.…”
Section: Methodsmentioning
confidence: 99%
“…While we hypothesize that, risk-sharing networks are formed to respond to health shocks (Fafchamps and Lund 2003;De Weerdt and Fafchamps 2011), several studies have reported the effect of social networks on health outcomes. For example, according to Nagayoshi et al (2014) and Chang et al (2017), social networks reduces the incident of stroke and coronary heart disease.…”
Section: Empirical Modelmentioning
confidence: 99%